2023
DOI: 10.1186/s12987-023-00436-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling idiopathic intracranial hypertension in rats: contributions of high fat diet and testosterone to intracranial pressure and cerebrospinal fluid production

Abstract: Background Idiopathic intracranial hypertension (IIH) is a condition characterized by increased intracranial pressure (ICP), impaired vision, and headache. Most cases of IIH occur in obese women of childbearing age, though age, BMI, and female sex do not encompass all aspects of IIH pathophysiology. Systemic metabolic dysregulation has been identified in IIH with a profile of androgen excess. However, the mechanistic coupling between obesity/hormonal perturbations and cerebrospinal fluid dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 101 publications
1
13
0
Order By: Relevance
“…To that end, we employed a female rat model of obesity to determine different aspects of CSF flow. We previously demonstrated that rats fed a high-fat diet became overweight and presented with an elevated ICP and reduced CSF drainage capacity [ 34 ], aligned with other studies also illustrating various other IIH features, including papilledema [ 33 , 78 ]. The extent of the ICP elevation in these high-fat diet-fed rats, however, did not recapitulate the minimum doubling of opening lumbar pressure detected in IIH patients [ 79 ], possibly because of the limited weight gain observed in this cohort.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…To that end, we employed a female rat model of obesity to determine different aspects of CSF flow. We previously demonstrated that rats fed a high-fat diet became overweight and presented with an elevated ICP and reduced CSF drainage capacity [ 34 ], aligned with other studies also illustrating various other IIH features, including papilledema [ 33 , 78 ]. The extent of the ICP elevation in these high-fat diet-fed rats, however, did not recapitulate the minimum doubling of opening lumbar pressure detected in IIH patients [ 79 ], possibly because of the limited weight gain observed in this cohort.…”
Section: Discussionsupporting
confidence: 76%
“…Obesity-induced neuroendocrine imbalances and metabolic inflammation, which may be present in IIH patients, could therefore be absent from this rat cohort at this early time point [ 81 ]. Alternatively, one could speculate that the high sugar/high fat diet employed in the earlier studies on rats becoming obese on such ‘Western diet’ [ 33 , 34 , 78 ] could modulate the ICP in ways that are currently unknown, but absent in the Zucker rats that become obese on regular chow. The diet on which rats, and potentially humans, become obese on, may thus have direct implications on CSF drainage and possibly other ICP-related physiological aspects including blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations